EFFECTS OF NITROGEN ION IMPLANTATION ON HARDNESS AND WEAR RESISTANCE OF THE Ti-6Al-4V ALLOY - Sudjatmoko, Lely Susita R.M., Wirjoadi, Bambang Siswanto (Website, 2015)
ABSTRACT EFFECT OF NITROGEN ION IMPLANTATION ON HARDNESS AND WEAR RESISTANCE OF THE Ti-6Al-4V ALLOY. The nitrogen ion implantation technique was chosen for improving surface hardness and the wear resistance properties of the Ti-6Al-4V alloy. An optimum nitrogen ion dose of 5 ´ 1016 ion/cm2 and ion energies of 70, 80 and 100 keV were used in this study. Microstructure, chemical composition and surface morphology studied using the technique of Scanning Electron Microscope (SEM) coupled with Energy Dispersive X-ray (EDX) and X-ray Diffraction (XRD). Analysis of the SEM-EDX micrographs and XRD diffraction patterns indicate that implanted layer on the surface of the Ti-6Al-4V alloy sample showed the presence of Ti2N and TiN phases which very hard and excellent wear resistance properties. Microhardness was measured by Vickers method, and the wear resistance was determined using the wear test equipment that work based on the amount of samples material lost during wear time. The results of measurements clearly indicate that implanted layer on surface of the Ti-6Al-4V alloy sample produced an optimum enhancement of hardness properties and wear resistance, and it occurs at ion energy of 80 keV and ion dose of 5 ´ 1016 ion/cm2. It is obtained that the hardness of implanted layer was increased by a factor of 2.1; whereas the wear resistance increased up to a factor of 27 compared to the standard sample. The increase in hardness and wear resistance of implanted layer are mainly due to the formation of Ti2N and TiN phases.